Four new species of the interstitial family Cobanocytheridae (Crustacea: Ostracoda) from central Japan - Higashi, Ryouichi; Tsukagoshi, Akira (Zootaxa, 2011)
Four interstitial cobanocytherid species are described from central Japan: Cobanocythere ikeyai sp. nov., Cobanocythere lata sp. nov., Paracobanocythere watanabei sp. nov. and Paracobanocythere grandis sp. nov. The reports of the two new Paracobanocythere species are the second and third for this genus since the original description of P. hawaiiensis Gottwald, 1983. Cobanocythere ikeyai sp. nov., and C. lata sp. nov., from Japan are morphologically more similar to the species of the “lanceolata group” by Gottwald (1983) and C. guttaeformis Gottwald, 1983 from the Galapagos Islands, respectively, rather than to other Cobanocythere species from Japan. The Japanese archipelago (eastern Eurasian Continent) and the Galapagos Islands (north-western South America) are separated by about 15,000 km from each other, and have never been adjoined throughout geological history. This fact, and also the morphological similarities between Cobanocythere species from Japan and the Galapagos Islands, suggests that this genus may have undergone global dispersal at several times in the past. Conversely, the genera Cobanocythere and Paracobanocythere are distributed not only around continents and continental islands but also around oceanic islands such as the Hawaiian and Galapagos Islands. We conclude, therefore, that the cobanocytherids seem to have been able to disperse long distances across oceans.